THE PHONOLOGICAL SYSTEM OF PELAGA DIALECT: A DESCRIPTIVE QUALITATIVE STUDY - ., Gusti Ngurah Rai Dwijantara; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujan untuk mendiskripsikan jumlah fonem dari dialek Pelaga. Penelitian deskriptif ini di desain dengan menggunakan penelitian deskriptif kualitatif. Tiga narasumber di pilih berdasarkan beberapa kriteria. Data di kumpulkan berdasarkan tiga word list, yaitu Swadesh, Budasi, and Holle. Data yang diperoleh di analisis secara deskriptif. Hasil dari penelitian menunjukan PD memiliki 55 fonem, yaitu: 6 vowel: /ʌ/, /i/, /u/, /e/, /o/, dan /∂/. 4 geminate vowels: /ʌʌ/, /II/,/ɔɔ/, and /ʊʊ/, 19 Consonants: /p/, /b/, /t/, /d/, /k/, /g/,/ʔ/,/s/, /ʧ/,/j/, /l/, /r/, /h/, /m/, /n/, /ñ/, / ŋ/, /w/, and /y/, and 19 Consonant clusters: /kl/,/pl/, /bl, /ml/, /tl/, /kr/, /mp/, /mb/, /nt/, /nd/,/nj/, /nc/, /ŋk/, /ŋs/, /ŋg/, /ŋw/, and /ŋky/. Tidak semua distribusi fonem PD ada di tiga posisi (initial. middle and final). Kata Kunci : Kata Kunci: Penelitian deskriptif kualitatif, sistem fonologi ,dialek Pelaga, fonem, vokal, diftong, konsonan and kelompok konsonan. The study aimed at describing the number of phonemes of Pelaga Dialect (PD). This descriptive study was designed by using a descriptive qualitative research. Three informant samples of PD were chosen based on a set of criteria. The data were collected based on three word lists: Swadesh, Budasi, and Holle’s Word Lists. The obtained data were analyzed descriptively. The result of the study shows that PD has 55 phonemes, namely: 6 vowels; /ʌ/, /i/, /u/, /e/, /o/, and /∂/. 9 Dipthongs; /ʌi/, /iʌ/, /ʌu/, /uʌ/, /ʌ∂/, /ʌe/, /ʌɔ/, /iu/, and /ɔʌ/, 4 geminate vowels; /ʌʌ/, /II/,/ɔɔ/, and /ʊʊ/, 19 Consonants; /p/, /b/, /t/, /d/, /k/, /g/,/ʔ/,/s/, /ʧ/,/j/, /l/, /r/, /h/, /m/, /n/, /ñ/, / ŋ/, /w/, and /y/, and 19 Consonant clusters; /kl/,/pl/, /bl, /ml/, /tl/, /kr/, /mp/, /mb/, /nt/, /nd/,/nj/, /nc/, /ŋk/, /ŋs/, /ŋg/, /ŋw/, and /ŋky/. Not all of phonemes distribute in three positions (initial, middle, and final position). keyword : Key Words: Descriptive qualitative study, the phonological system, Pelaga dialect, phonemes, vowel, diphthong, consonant cluster and consonant.